Answer:
-(3x^2 + 16x + 5)
-(3x+1)(x+5)
Step-by-step explanation:
-1(3x^2+15x+x+5)
-1(3x^2+16x+5)
-3x^2-16x-5
9514 1404 393
Answer:
3. vertical stretch by a factor of 2; shift right 1 and down 1
4. shift left 4 and up 4 (no stretch or shrink)
Step-by-step explanation:
The vertex form equation is ...
y = a(x -h)^2 +k
It represents a vertical stretch of the parent function by a factor of 'a', a right shift of 'h', and an upward shift of 'k'.
Compare the the given equations to the above form to see the transformations.
__
3. (a, h, k) = (2, 1, -1) ⇒ vertical stretch by a factor of 2; shift right 1, down 1
4. (a, h, k) = (1, -4, 4) ⇒ no vertical stretch; shift left 4, up 4
/ means divide, so U( an unknown value ) / 6 = 9. to get the answer, simply multiply 6 x 9